Erratum to: Higher-order optimality conditions for weakly efficient solutions in nonconvex set-valued optimization (Optim Lett, (2010) 4, (425-437), 10.1007/s11590-009-0170-5) - Wang, Q.; Li, S.; Teo, Kok Lay (2012)
The online version of the original article can be found at http://doi.org/10.1007/s11590-009-0170-5